Safety evaluation of the food enzyme glucan 1,4‐α‐maltohydrolase from the genetically modified Saccharomyces cerevisiae strain LALL‐MA+ - EFSA FEZ Panel (EFSA Panel on Food Enzymes); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize de Lourdes Marzo Solano; Monika Sramkova; et al. (EFSA Journal)
Abstract The food enzyme glucan 1,4‐α‐maltohydrolase (4‐α‐d‐glucan α‐maltohydrolase; EC 3.2.1.133) is produced with the genetically modified Saccharomyces cerevisiae strain LALL‐MA+ by Danstar Ferment AG. The genetic modifications do not give rise to safety concerns. The food enzyme is free from viable cells of the production organism and its DNA. It is intended to be used in the processing of cereals and other grains for production of baked products. Dietary exposure was estimated to be up to 0.014 mg TOS/kg body weight per day in European populations. Given the QPS status of the production strain and the absence of concerns resulting from the food enzyme manufacturing process, toxicity tests were considered unnecessary by the Panel. A search for the identity of the amino acid sequence of the food enzyme to known allergens was made and four matches were found, three with respiratory allergens and one with an allergen from mosquito (injected). The Panel considered that the risk of allergic reactions upon dietary exposure cannot be excluded, but the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns, under the intended conditions of use.